Increased body fatness adversely relates to 24-hour urine pH during childhood and adolescence: evidence of an adipo-renal axis. Issue 5 (17th April 2019) - Hua, Yifan; Krupp, Danika; Esche, Jonas; Remer, Thomas
ABSTRACT: Background: Reduced net acid excretion (NAE) capacity indicates a decrease in renal function. This reduction manifests as a disproportionally low 24-h urine pH in relation to the sum of actually excreted ammonium and titratable acidity by the kidney. Objective: The aim of this study was to test the hypothesis that higher body fatness is one determinant of kidney function impairment with a lowered urine pH even at a young age. Methods: NAE, pH, urea, and creatinine were measured in 24-h urine samples from 524 healthy children and adolescents (aged 6–17 y) participating in the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study. Body fatness was assessed anthropometrically by body mass index-standard deviation score (BMI-SDS), fat mass index (FMI), body fat % (BF%), and waist circumference (WC). Multivariable linear and mixed linear regressions were used to examine cross-sectionally ( n = 524 urine samples; age groups: 6–8, 9–11, 12–14, 15–17 y) and longitudinally ( n = 1999 urine samples) the associations of body fatness with 24-h urine pH as the outcome variable, respectively. Results: After adjusting for the kidneys' total net acid load (24-h urinary NAE) and further relevant covariates, FMI showed significant inverse relations with urinary pH in all 4 age groups, and BMI-SDS, BF%, and WC each in 3 out of these 4 groups ( P ≤ 0.02). Longitudinal results substantiated these interindividual relations and further showed intraindividual increases in body fatness to be paralleled by urine pH decreases ( P ≤ 0.0002). Conclusions: Independent of underlying acid load, an early increase in body fatness is associated with increased free proton excretion, and thus with a decline in the kidney's acid excretion function, which could potentiate the risk of renal nephrolithiasis.